2021
DOI: 10.3389/fonc.2021.710694
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of the DNA Repair Gene Signature in Head and Neck Squamous Cell Carcinoma

Abstract: PurposeTo construct a prognostic signature composed of DNA repair genes to effectively predict the prognosis of patients with head and neck squamous cell carcinoma (HNSCC).MethodsAfter downloading the transcriptome and clinical data of HNSCC from the Cancer Genome Atlas (TCGA), 499 patients with HNSCC were equally divided into training and testing sets. In the training set, 13 DNA repair genes were screened using univariate proportional hazard (Cox) regression analysis and least absolute shrinkage and selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
1
0
0
Order By: Relevance
“…Furthermore, we found that the lowrisk group was more activated as a whole in tracking the analysis of the tumor immunophenotype, except step 1 release of cancer cell antigens and step 6 recognition of cancer cells by T cells (Liwen et al, 2018). Furthermore, the low-risk group had a higher expression of immune checkpoints and markers, such as PD-L1 and HLA-ABC, which is similar to several reports by Ming et al (2021). Therefore, the results have supposed that patients in the low-risk group would benefit more from immune checkpoint blocking therapy.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, we found that the lowrisk group was more activated as a whole in tracking the analysis of the tumor immunophenotype, except step 1 release of cancer cell antigens and step 6 recognition of cancer cells by T cells (Liwen et al, 2018). Furthermore, the low-risk group had a higher expression of immune checkpoints and markers, such as PD-L1 and HLA-ABC, which is similar to several reports by Ming et al (2021). Therefore, the results have supposed that patients in the low-risk group would benefit more from immune checkpoint blocking therapy.…”
Section: Discussionsupporting
confidence: 89%